Understanding Health Literacy in Patients Receiving Hematopoietic Stem Cell Transplantation. - Cohen, Marlene Z.; Jenkins, Debra; Holston, Ezra C.; Carlson, Elizabeth D. (Oncology Nursing Forum, 2013)
Purpose/Objectives: To describe the meaning of patients' experiences with hematopoietic stem cell transplantation (HSCT), with a focus on health literacy.Research Approach: A hermeneutic phenomenologic approach that combines descriptive and interpretive methods.Setting: A National Cancer Institute-designated comprehensive cancer center in the southern United States.Sample: 60 individuals who underwent HSCT; 20 Latino, 20 African American, and 20 Caucasian.Methodologic Approach: In-depth interviews were conducted on five separate occasions. Interviews and analysis of verbatim transcripts used phenomenologic techniques.Findings: The themes were as follows: they did not tell me, decision dilemmas, fears of dying, tough symptoms and side effects, and relying on others. These themes were found in all ethnic groups, both genders, and at all time points.Conclusions: The themes from this study demonstrate that health literacy concerns are vital to patients' understanding, decision making, and having active roles in their health care. Assessing patients' understanding is important and requires a comprehensive approach because patients may not know what they need to ask and may not feel comfortable asking or raising objections because their fears, particularly that of dying, are barriers.Interpretation: This article provides evidence that health literacy is not a simple function of age, ethnicity, race, or education. Health literacy and communication concerns require a more nuanced approach to provide optimal patient-centered outcomes.Knowledge Translation: Understanding patients' perspectives is vital to knowing what to communicate, how to communicate, and when to provide information. Providing information in a way patients can understand reduces risks for negative outcomes. A comprehensive assessment of patients' understanding using improved education materials, clearer forms and communication techniques, teach-back methods, and reinforcement is needed to improve communication, particularly when illness and treatment evoke fears.